Water sludge reuse as a geotechnical component in road construction: Experimental study - Fiore, Fabiana Alves [UNESP]; Rodgher, Suzelei [UNESP]; Koga Ito, Cristiane Yumi [UNESP]; Bardini, Vivian Silveira dos Santos; Klinsky, Luis Miguel Gutiérrez (Elsevier, 2022)
In Brazil, the process of surface water potabilization for public supply generates sludge, but information on this waste is scarce, and its disposal in landfills and waterways, without prior treatment, generates pollution. This experimental study evaluated the incorporation of aluminum and ferric sludge, commonly generated in Brazil, into different soils for road pavement infrastructure. Sludge generated in two water treatment plants in the state of São Paulo was characterized regarding risks to human health and the environment and individually incorporated into clayey sand soil and sandy soil in proportions of 25 and 50%. Evaluation of the mechanical tests of the soil sludge mixtures and their suitability for road construction found that i) all percentages of aluminum and ferric sludge incorporated into clayey sand soils and sandy soil met the mechanical standards for use in embankment; ii) aluminum sludge incorporated into sandy soils proved to be suitable for use in pavement subbase; iii) the percentual incorporation is higher than previous research; iv) the use of sludge as a partial replacement for virgin soil makes road construction cleaner. Analyses of variance on the mechanical properties of the soil-sludge mixtures showed that soil type is the only factor influencing this variable. Only the interaction of water treatment sludge (WTS) type with the other factors is significant for the CBR and Swell data.
Keywords: Reuse of sludge; Road construction; Water treatment sludge